A situation model of integrated health information platform in India: an anticipated review - Ka, Mogan; Periyasamy, Aravind Gandhi; U., Venkatesh; Kishore, Jugal (International Journal Of Community Medicine And Public Health, 2020)
Health system in India is fragmented with different kinds of health care providers engaged in the delivery of health services across rural and urban areas. The integration of health information in a single platform aids in strengthening the public health surveillance systems, better decision support system, improvement in the efficiency and effectiveness in the context of health education and monitoring. In order to integrate the public health data and strengthen the surveillance and monitoring, the integrated health information platform (IHIP) was launched as pilot project following the report of the joint monitoring mission of the World Health Organization. IHIP integrates the electronic health records of the citizens on a pan-India basis aids in providing a comprehensive health profile of the population. Integrated disease surveillance programme (IDSP) module of integrated health information platform (IHIP) was the earliest initiative of integrating various health programmes. It is a web-based real-time, village wise, case-based electronic health information system that will aim to provide details about epidemic-prone diseases with geographical information system (GIS) thus reducing the morbidity and mortality and lessening disease burden in the populations. GIS information obtained via IHIP provides information in the form of a geographical map as interface data with real-time monitoring thus contributes to Geospatial Epidemiology in addition to information by IDSP. This article aims to describe the anticipated model of IHIP in the context of providing ‘One Health’ by the integration of health sectors.